Democracy and ethno-religious conflict in Iraq - Andreas Wimmer (University of Bonn, Center for Development Research (ZEF), 2003)
How can an escalation of tensions between the major ethno-religious groups be avoided in a democratizing Iraq? The first section explains why and under which conditions democratization may stir up, rather than palliate ethnic conflicts: when networks of civil society organizations have not yet developed and if the state is too weak and poor to be able to treat all citizens equally. The second section looks at the political history of Iraq, which is characterized by increasing fragmentation and conflict along ethnic lines. Pan-Arabism became the official state ideology and Shii, Kurds, Jews and Christians were excluded from positions of power and gradually driven out of the officers corps and the higher ranks of the administration. This Arabization of the Iraqi state was contested right from the beginning, as a review of the history of Kurdish and Shii uprisings will show. Throughout this history, the divisions along ethno-religious lines have deepened. Cross-ethnic parties (such as the Communists) and organizations have split along these lines too. Rising levels of repression increasingly directed against the civilian population have further estranged Kurds, Shiis and Christians from the Iraqi state and bolstered support for their respective ethno-religious organizations. Elections are likely to stir up ethno-religious conflicts in the future, if democratic institutions are not designed to foster moderation and compromise. Several such designs are discussed in the last section and the following will be recommended: an electoral system that favors vote pooling across ethnic lines; federalism on a non-ethnic basis with a strong component of fiscal decentralization; a strong regime of minority rights and a judicial apparatus capable of enforcing the rule of law. Elections should come last, not first in the process of institutional transformation. International institutions can provide the legitimacy for the continued outside supervision and support that are needed, during years to come, to make democracy sustainable.
Keywords: 330; Political Economy